Hippocampus-Based Mitochondrial Respiratory Function Decline Is Responsible for Perioperative Neurocognitive Disorders - He, Keqiang; Zhang, Juan; Zhang, Wei; Wang, Sheng; Li, Dingfeng; Ma, Xiaolin; Wu, Xiaofan; Chai, Xiaoqing; Liu, Qiang (Frontiers in Aging Neuroscience, 2022)
Perioperative neurocognitive disorders (PND), a cognitive dysfunction occurs with higher incidence in elderly patients. However, the pathological mechanism of PND and effective treatment remain elusive. We generated a PND mouse model by providing wild-type mice a surgical trauma, in our case we used tibial fracture to investigate PND pathology. Mice at age of 7~8 months were randomly divided into two groups, surgery (tibial fracture) group and control (sham) group. All mice were subjected to anesthesia. We examined the transcriptome-wide response in the hippocampus, a brain region that is tightly associated with memory formation, of control mice and mice treated with surgical trauma at day (d) 1 and d 3 after surgery procedure. We observed reduced transcript levels of respiratory complex components as early as d 1 after surgery, subsequent protein changes were found at d 3 after surgical trauma. Consequently, the activities of multiple respiratory complexes were reduced, and ATP production was decreased in the hippocampus of mice with surgical operations, supporting respiratory chain function was impaired. In support of these conclusions, mitochondrial membrane potential (MMP) levels were decreased and reactive oxygen species (ROS) levels were significantly increased. Mechanistically, we demonstrate that surgery induced a significant increase in cytokine IL-1β levels at d 1 after surgery, which concomitantly occurred with transcript changes in these respiratory complex components. We further uncover that transcriptional factors PGC-1α and NRF-1 were responsible for observed transcript changes in mitochondrial complex components. Importantly, HT22 cells treated with cytokine IL-1β resulted in similar reductions in PGC-1α and NRF-1, subsequently led to both decreased transcript and protein levels of respiratory complex components. Consequently, respiratory function was impaired in HT22 cells treated with IL-1β. Taken together, we demonstrate that reductions in respiratory complex components and subsequent impairment in mitochondrial functions serve as a novel mechanism for PND pathology, providing a potential therapeutic target for PND treatment.